INFLUENCE OF PILATES METHOD IN THE TREATMENT AND QUALITY OF LIFE IN WOMEN WITH URINARY INCONTINENCE (Fiep Bulletin - online, 2014)
The aim of this study was to investigate the influence of Pilates Soil treatment and QOL in women with UI. The sample was composed of 6 women with a mean age of 61.3 years (SD ± 10.46). Were evaluated through the QOL questionnaire ICIQ - SF and perineal muscle strength through physical examination with perineometer before and after physical therapy. Treatment consisted of 16 sessions of exercises based on Pilates Solo, performed 2 times per week, lasting 1 hour each. It was observed that the Pilates Method soil influenced positively both QOL and the strength of the pelvic floor muscles of patients, reducing the number of exchanges and the use of protective underwear, reducing the amount, the situations and the frequency of urinary incontinence and improving the impact that UI brings the QOL of patients. We conclude that the Pilates Method can be used as a physiotherapy technique for strengthening the perineal muscles and awareness of these muscles, improving its function and consequently improving the QOL of women with UI.
Keywords: Urinary Incontinence; Pilates; Quality of Life